In vitro assays and clinical trials in red blood cell aging: Lost in translation. Issue 3 (June 2015) - Prudent, Michel; Tissot, Jean-Daniel; Lion, Niels
Abstract: The age of erythrocyte concentrates (EC) in transfusion medicine and the adverse outcomes when transfusing long-term-stored EC are highly controversial issues. Whereas the definition of a short-term-stored EC or a long-term-stored EC is unclear in clinical trials, data based on in vitro storage assays can help defining a limit in addition of the expiration date. The present review merges together these data in order to highlight an EC age cut-off and points out potential misleading consideration. The analysis of in vitro data highlights the presence of reversible and irreversible storage lesions and demonstrates that red blood cells (RBC) exhibit two limits during storage: one around 2 weeks and another one around 4 weeks of storage. Of particular importance, the first lesions to appear, i.e. the reversible ones, are per se reversible once transfused, whereas the irreversible lesions are not. In clinical trials, the EC age cut-off for short-term storage is in general fewer than 14 days (11 ± 4 days) and more disperse for long-term-stored EC (17 ± 13 days), regardless the clinical outcomes. Taking together, EC age cut-off in clinical trials does not totally fall into line of in vitro aging data, whereas it is the key criteria in clinical studies. Long-term-stored EC considered in clinical trials are not probably old enough to answer the question: "Does transfusion of long-term-stored EC (older than 4 weeks) result in worse clinical outcomes?" Depending on ethical concerns and clinical practices, older EC than currently assayed in clinical trials should have to be considered. These two worlds trying to understand the aging of erythrocytes and the impact on patients do not seem to speak the same language.